Assistance of the Youth Organization Community in the Construction of an Integrated Road as an Artificial Recharge for the Slopes of Mount Manglayang through a Participatory Action-Research Approach in Babakan Cikeruh Village - Riyanto Adji; Haris Herdiansyah; Teuku Rezasyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Youth is an agent of change for a region, but if youth are affected by the environment and technology, then youth will not be able to make a good contribution to the region, therefore in order for youth to be more productive, it is necessary to be guided, nurtured and directed. As happened to the youth in RW 14 Kampung Babakan CIkeruh, Cimekar Village, Cileunyi Bandung, where most of the youth have been influenced by gadgets and wrong associations. Shifting the role of youth from being productive, there needs to be intensive assistance and empowerment, so that they are able to contribute to their region. In order to be able to assist and empower youth, it is necessary to use a participatory method for youth through youth organizations. The participatory method used is a participatory action study, this method is a research method that uses action/experience steps, reflection, integration, and planning. The use of the participatory study-action method aims to build awareness of youth youth groups in road construction, and through mentoring and empowering youth youth organizations it is hoped that they will be able to realize the wishes of the residents, namely the realization of good and decent roads. proposals for road construction/remediation activities with a length of 50 m and a width of 3 m which are integrated with infiltration wells that function as artificial recharge for dug wells to become a source of clean water for residents around the road. funds for the implementation of its development by exploring the potential around the RW 14 area. By utilizing the existing potential, both the potential of natural resources and the potential of human resources, the road is realized. After the implementation of the work, the youth were directed to compile an accountability report as proof of transparency with the citizens. The results of the mentoring and empowerment of RW 14 youth organizations in general gave a significant change for RW 14 youth youth organizations who initially only played gadgets to become youths who were able to make a real contribution to their area, namely being able to realize the dreams of the community by implementing road construction with concrete rebates.